ARABLE CROP FARMERS’ ACCESS TO RURAL INFRASTRUCTURE IN IREPODUN LOCAL GOVERNMENT AREA, KWARA STATE, NIGERIA - AJALA, A. O.; OGUNJIMI, S. I.; ALABI, O. O; ADEWUMI, O. T.; OLATUNJI, E. A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2023)
The study investigated the accessibility to rural infrastructure among arable crop farmers in Irepodun Local Government Area, Kwara State. Specifically, the study determined the level of availability and accessibility of rural infrastructure in the study area and identified the constraints to them. A multistage sampling technique was used to select 120 arable crop farmers from six (6) rural communities of the LGA. Data was analyzed using descriptive and inferential statistics. The results show that the mean age of the farmers was   49±11.91 years. The result depicts a male dominance (61.7%) in arable crops farming while 38.3% of the farmers were females in the study area. The majority (91.7%) of the arable crop farmers were married with a mean family size of about 6 persons while a good majority (73.4%) of the respondents were literate. 100% of the respondents engaged in mixed cropping systems with a mean farm size of 4.023. Age (r=0.587), household size (r=0.496), and years of farming experience, (r=0.340) had a significant relationship with access to rural infrastructure at   0.05 level of significance. It is concluded that rural infrastructures are moderately available and accessible and are in moderately good working conditions but not enough to create an enabling environment for increased productivity. It is recommended that concerted efforts should be made by rural development stakeholders (government, NGOs, and the private sector) to improve the provision, maintenance, and sustenance of the infrastructures for a sustainable rural livelihood.